Analysis Of Supply Chain Development Strategy For Ornamental Corals Agribusiness, UKM Gapekhi Makassar - Andi Baso Adil Natsir; Mauli Kasmi; Asti Sugiarti; Sitti Fakhriyyah (International Journal of Business and Quality Research, 2023)
This research aims to understand and analyze the supply chain development strategy for ornamental corals agribusiness in UKM Gapekhi Makassar, including the upstream supply chain, internal supply chain, and downstream supply chain. The research method used is a case study. The research location and respondents were purposively selected from UKM Gapekhi Makassar and the distribution areas of ornamental corals in Jakarta, Java, and Bali. The data analysis methods used include Benchmarking Supplier analysis, IFE Matrix analysis, EFE Matrix analysis, IE Matrix analysis, SWOT Matrix analysis, Data Envelopment Analysis (DEA), and analysis of marketing distribution channel margin and efficiency. The research findings indicate that the company receives the highest supply of ornamental corals from the supplier Rezky Bahari, while the highest number of rejected corals comes from the supplier Hidayah. The highest number of coral shipments is from Supplier Banyu Samudra Lestari, while the lowest number of coral shipments is from Supplier Virly Jaya Abadi. The IFE Matrix score is 3.416, the EFE Matrix score is 3.400, the IE Matrix indicates the company is in Cell 1, and the SWOT Matrix produces several strategies that can be implemented by the company to foster its development. The marketing distribution channel flow starts from the producer (UKM Gapekhi), to the distributor (Coordinator), to the wholesaler/depot (Leader), to the retailer (Loper), and finally to the end consumer (Buyer). The DEA analysis reveals inefficient areas in the distribution of marketing products. The margin and efficiency of the marketing distribution channel are good and efficient, with an average product marketing percentage of 68.25%.